Single‐nucleotide polymorphisms are associated with cognitive decline at Alzheimer's disease conversion within mild cognitive impairment patients. Issue 1 (23rd April 2017) - Lee, Eunjee; Giovanello, Kelly S.; Saykin, Andrew J.; Xie, Fengchang; Kong, Dehan; Wang, Yue; Yang, Liuqing; Ibrahim, Joseph G.; Doraiswamy, P. Murali; Zhu, Hongtu
Abstract: Introduction: The growing public threat of Alzheimer's disease (AD) has raised the urgency to quantify the degree of cognitive decline during the conversion process of mild cognitive impairment (MCI) to AD and its underlying genetic pathway. The aim of this article was to test genetic common variants associated with accelerated cognitive decline after the conversion of MCI to AD. Methods: In 583 subjects with MCI enrolled in the Alzheimer's Disease Neuroimaging Initiative (ADNI; ADNI‐1, ADNI‐Go, and ADNI‐2), 245 MCI participants converted to AD at follow‐up. We tested the interaction effects between individual single‐nucleotide polymorphisms and AD diagnosis trajectory on the longitudinal Alzheimer's Disease Assessment Scale‐Cognition scores. Results: Our findings reveal six genes, including BDH1, ST6GAL1, RAB20, PDS5B, ADARB2, and SPSB1, which are directly or indirectly related to MCI conversion to AD. Discussion: This genome‐wide association study sheds light on a genetic mechanism of longitudinal cognitive changes during the transition period from MCI to AD.